Pengaruh Dana Tabarru’ Dan Beban Operasional Terhadap Pertumbuhan Aset: Studi Kasus Asuransi Syariah di Indonesia yang terdaftar di Otoritas Jasa Keuangan Periode 2017-2021 - Rafiqul Amin; Fithrah Kamaliyah (Jurnal Literasi Akuntansi, 2023)
This study aims to test and prove the effect of Tabarru’ funds and operating expenses on asset growth (a case study of Islamic insurance in Indonesia registered with the financial services authority for the period 2017-2021. The type of research used is quantitative. The type of data used is secondary data in the form of reports sharia insurance companies registered with the Financial Services Authority in 2017-2021. Samples were collected using the purposive sampling method. The number of companies used as research samples were 13 companies with a research period of 5 years of observation, so that a total of 65 research samples were obtained Processing data using the Program Eviews Statistics 9. Furthermore, by carrying out various tests including, descriptive statistical tests, model tests, model selection tests, classic assumption tests and hypothesis tests, so the research test results prove that: Tabarru’ funds and operating expenses simultaneously affect the growth of insurance case study assets sharia registered with the financial services authority for the period 2017-2021. The Tabarru’ fund variable partially has no effect on the growth of sharia insurance assets. The operating expense variable partially affects the growth of sharia insurance assets in 2017-2021. Keywords: Tabarru’ Fund; Operating Expenses; Asset growth.